17.7k views
5 votes
Y= -3x +5
5x -4y = -3

User Polash
by
5.7k points

1 Answer

3 votes

Answer:

The solution of the system of equations is the point (1,2)

Explanation:

It is required to solve the system of equations:

y= -3x + 5

5x - 4y = -3

So, substitute with y from the first equation at the second equation:

∴ 5x - 4(-3x + 5) = -3

Solve for x

∴ 5x + 12x - 20 = -3

∴ 17x = -3 +20 = 17

∴ x = 17/17 = 1

∴ y = -3 * 1 + 5 = -3 + 5 =2

So, the solution of the system of equations (1,2)

Another solution:

The give system of equations can be solved by graph both of them.

So, the solution will be the intersection between the lines.

See the attached figure.

Y= -3x +5 5x -4y = -3-example-1
User Wilmer SH
by
4.8k points